Exploring a framework for the holistic well-being of orphaned learners in Lesotho secondary schools - Mahanetsa, Tsooana ‘Mampitla (University of the Free State, 2024)
The promotion of the well-being of orphaned leaners is a contemporary issue and has gained momentum in recent years. The continued challenges of orphaned learners necessitate a change in strategies to address the overall challenges of learners and promote their holistic well-being. This study aims to explore the framework for holistic well-being of school-going orphans in Lesotho schools. A qualitative interpretive paradigm was used to explore the experiences of teachers and orphaned learners about a framework that could facilitate the holistic well-being of orphaned learners in Lesotho secondary schools. The study employed theoretical triangulation of an asset based theory and the ecological systems theory as a lens which focused and guided the study. Convenience sampling and purposive sampling were utilised to select the schools and participants of the study. The participants were five orphaned learners and five teachers from two secondary schools in Lesotho. Data were collected through the use of semi-structured interviews and analysed thematically. The findings of the research uncovered a number of issues. Poverty and a lack of academic resources and financial support, a lack of psychosocial support, feelings of sadness and depression were identified as some of the challenges that impede the holistic well being and negatively affect academic performance. The study also revealed that holistic well-being encapsulates support in all aspects of life, such as the provision of life skills, the acquisition of learning resources and having basic needs met, self acceptance, and a conducive environment. Lastly, the study identified the following strategies and structures for the facilitation of the holistic well-being of orphaned learners: the provision of counselling and psychosocial support, empowering the orphans’ guardians to manage their unique situation, collaborative care and support between stakeholders, and academic support and mentorship.
Thesis (Ph.D. (Community Psychology of Education))--University of the Free State, 2024